2019
DOI: 10.1029/2018ja026241
|View full text |Cite
|
Sign up to set email alerts
|

Fabry‐Perot Interferometer Observations of Thermospheric Horizontal Winds During Magnetospheric Substorms

Abstract: The high‐latitude ionosphere‐thermosphere system is strongly affected by the magnetospheric energy input during magnetospheric substorms. In this study, we investigate the response of the upper thermospheric winds to four substorm events by using the Fabry‐Perot interferometer at Tromsø, Norway, the International Monitor for Auroral Geomagnetic Effects magnetometers, the EISCAT radar, and an all‐sky camera. The upper thermospheric winds had distinct responses to substorm phases. During the growth phase, westwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 82 publications
5
29
0
Order By: Relevance
“…If we assume that the observed wind variations occurred during 30 min, then the amplitudes of acceleration rates of zonal winds were 0.0097-0.0272 m/s 2 (+ 17.5 m/s of R1, + 48.9 m/s of R2). These values are comparable with the acceleration rates of zonal winds (0.0189-0.1 m/s 2 ) during/near the expansion phase as summarized in Table 2 of Cai et al (2019).…”
Section: Polar Plots Of Wind Variations At Local Substorm Onsetssupporting
confidence: 85%
See 1 more Smart Citation
“…If we assume that the observed wind variations occurred during 30 min, then the amplitudes of acceleration rates of zonal winds were 0.0097-0.0272 m/s 2 (+ 17.5 m/s of R1, + 48.9 m/s of R2). These values are comparable with the acceleration rates of zonal winds (0.0189-0.1 m/s 2 ) during/near the expansion phase as summarized in Table 2 of Cai et al (2019).…”
Section: Polar Plots Of Wind Variations At Local Substorm Onsetssupporting
confidence: 85%
“…It seems that there were no strong prehistory plasma convection activities that can contribute to the observed wind variations at local substorm onsets. Cai et al (2019) used the same FPI (630.0 nm) at Tromsø to study thermospheric wind variations during different substorm phases. The four substorm events in their study are different from our four events and have stronger magnetic field variations.…”
Section: Polar Plots Of Wind Variations At Local Substorm Onsetsmentioning
confidence: 99%
“…The E region winds retaining an eastward component (aligned with E × B drifting plasma) could in part be due to the long E region ion‐drag timescales discussed earlier but also reflect that the ion‐neutral collision frequency at lower altitudes is much higher when compared to F region altitudes. Thus, E region winds better represent the strengthening westward electrojet current during substorm expansion, in agreement with Cai et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Large increases in Joule heating due to the sudden injection of auroral energy trigger atmospheric gravity waves (AGWs) (Hines, 1960), which cause neutral wind disturbances to propagate to lower latitudes, and potentially even into the opposite hemisphere, as observed in simulations (Fuller‐Rowell et al, 1994; Richmond & Matsushita, 1975). Other model simulations (e.g., Fuller‐Rowell & Rees, 1984, and numerous since) found that ion drag was enhanced throughout the entire polar region during an isolated substorm, and Cai et al (2019) noted similar strengthening of ion drag during substorm expansion on the mesoscale, using ground‐based FPI observations. So far, however, observations of the effect of substorms on neutral dynamics at both E and F region altitudes, with regards to ion drag from plasma convection, have not been examined.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation